Evaluation of Sofi Tissue Differences between Different Skeletal Anomalies in Sagittal Direction - Seher Gündüz-Arslan; Kamile Keskin; Atılım Akkurt; Jalen Devecioğlu-Kama (Galenos Yayinevi, 2008)
The aim of this study is to evaluate the cephalometric soft tissue differences of early adults in sagittal direction. Our study consists of 63 patients' lateral cephalograms who referred to University of Dicle Faculty of Dentistry for orthodontic treatment (Class I: 23, Class II: 19, Class III: 21). The main age was 19.28 years. 24 angular and linear measurements were performed in cephalometric radiographs of patients. According to Mann Whitney U test only the PMA angle showed statistically significant differences in comparison of Class I and II patients. In comparison of adult Class I and III patients; Class III patients were showed greater values in; A-UpSulcus, Uplip-E Line, MLA and PMA parameters. In comparison of adult Class II and III patients with normal vertical pattern, PTV-Nasaltip and PTV-UpSulcus parameters were greater for Class II patients. Regardless of abnormality in skeletal tissue of underlying soft tissue it still has a great tendency to return to normal. We observed that compensatory mechanism works remarkably especially for soft tissues of Class II anomaly groups.